2017
DOI: 10.3390/molecules22071087
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and In Vitro Anticancer Activity of Novel Dehydroabietic Acid-Based Acylhydrazones

Abstract: In order to develop novel chemotherapeutic agents with potent anticancer activities, a series of dehydroabietic acid (DHA) derivatives bearing an acylhydrazone moiety were designed and synthesized by the condensation between dehydroabietic acylhydrazide (3) and a variety of substituted arylaldehydes. The inhibitory activities of these compounds against CNE-2 (nasopharynx), HepG2 (liver), HeLa (epithelial cervical), and BEL-7402 (liver) human carcinoma cell lines were evaluated by 3-(4,5-dimethylthiazol-2-yl)-2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 29 publications
0
16
0
Order By: Relevance
“…For example, a series of 3-ethoxy-4-hydroxybenzaldehyde oxime esters were synthesized and evaluated for their in vitro antifungal activity against three pathogenic fungi and antibacterial activity against three bacterial strains, and the structure-activity relationship was also preliminarily summarized [ 26 ]. In continuation of our interest in the bioactive properties of natural product-based compounds [ 27 , 28 , 29 , 30 , 31 , 32 , 33 ], a series of novel 3-caren-5-one oxime esters were designed and synthesized by integrating bioactive oxime esters into the skeleton of 3-carene. Structural characterization and antifungal evaluation of all the title compounds were carried out as well.…”
Section: Introductionmentioning
confidence: 99%
“…For example, a series of 3-ethoxy-4-hydroxybenzaldehyde oxime esters were synthesized and evaluated for their in vitro antifungal activity against three pathogenic fungi and antibacterial activity against three bacterial strains, and the structure-activity relationship was also preliminarily summarized [ 26 ]. In continuation of our interest in the bioactive properties of natural product-based compounds [ 27 , 28 , 29 , 30 , 31 , 32 , 33 ], a series of novel 3-caren-5-one oxime esters were designed and synthesized by integrating bioactive oxime esters into the skeleton of 3-carene. Structural characterization and antifungal evaluation of all the title compounds were carried out as well.…”
Section: Introductionmentioning
confidence: 99%
“…Particularly, it is reported that numerous NO-donating hybrids have the potential to provide novel anticancer candidates with low toxicity and high efficacy against drug-resistant cancers. [22][23][24][25][26][27] Enlightened by these findings, together with our previous studies on the modification of natural products, [28][29][30][31] a modification via integrating DHAA and nitrate pharmacophore into one molecule to generate a novel dehydroabietic acid NO donor hybrids was conducted. The screening of the cytotoxicity of these hybrids against four human cancer cell lines and normal human cell were carried on.…”
Section: Introductionmentioning
confidence: 99%
“…Our research group has recently reported the synthesis of a series of structurally modified 3-carene derivatives and found that some of the title compounds exhibited excellent antifungal activity [21]. Herein, as continuation of our work on natural product-based bioactive compounds [22,23,24,25,26,27], a series of novel 3-caren-5-one oxime sulfonates were designed and synthesized by integrating bioactive oxime sulfonates into the skeleton of 3-carene. Structural characterization and antifungal evaluation of all the target compounds were carried out as well.…”
Section: Introductionmentioning
confidence: 99%